Rancang Dan Bangun Game Edukasi Anak-Anak Berbasis Android Dengan Unity Menggunakan Metode Game Development Life Cycle - Raden Muhammad Mirza Prasetyo; Hadi Syaputra; Widya Cholil; Siti Sauda (Jurnal Nasional Ilmu Komputer, 2021)
Technology is growing with the times, relentlessly and constantly moving forward to make new breakthroughs in all aspects of life. The IEA report in the Study of Reading Literacy states that the ability of elementary school children in Indonesia is very low. Of the 31 countries studied, Indonesia was ranked 30th. Based on the explanation of the background above, the researchers formulated the problem in this study, namely how to design and build an Android-based educational game with unity using the Game development life cycle (GDLC). This research was conducted in August 2021 in 9/10 Ulu Village, Plaju District, Palembang with a sample of 10 children. The research method uses Action Research and application development methods use GDLC. The results of testing the game system with blackbox that can be operated smoothly and for the results of testing the feasibility of games with the results of 84.6% in the appropriate category, the results of development with Unity and GDLC succeeded in creating learning media based on android games quite well.